One Scaffold, Different Organelle Sensors: pH‐Activable Fluorescent Probes for Targeting Live Microglial Cell Organelles. (13th October 2021) - Jethava, Krupal P.; Prakash, Priya; Manchanda, Palak; Arora, Harshit; Chopra, Gaurav
Abstract: Targeting live cell organelles is essential for imaging, understanding, and controlling specific biochemical processes. Typically, fluorescent probes with distinct structural scaffolds are used to target specific cell organelles. Here, we have designed a modular one‐step synthetic strategy using a common reaction intermediate to develop new lysosomal, mitochondrial, and nucleus‐targeting pH‐activable fluorescent probes that are all based on a single boron dipyrromethane scaffold. The divergent cell organelle targeting was achieved by synthesizing probes with specific functional group changes to the central scaffold resulting in differential fluorescence and pKa . Specifically, we show that the functional group transformation of the same scaffold influences cellular localization and specificity of pH‐activable fluorescent probes in live primary microglial cells with pKa values ranging from ∼3.2–6.0. We introduce a structure‐organelle‐relationship (SOR) framework to target nuclei (NucShine ), lysosomes (LysoShine ), and mitochondria (MitoShine ) in live microglia. This work will result in future applications of SOR beyond imaging to target and control organelle‐specific biochemical processes in disease‐specific models. Abstract : How can a common synthetic intermediate be transformed by different functional groups to target different cell organelles? We evaluated the structure‐organelle‐relationship (SOR) of pH‐activable fluorescent probes synthesized from the same synthetic intermediate to target nuclei, lysosomes, and mitochondria in live microglial cells.